Energy metabolism of white adipose tissue and insulin resistance in humans - Bódis, Kálmán; Roden, Michael (European journal of clinical investigation, 2018)
Background Insulin resistance not only occurs in obesity, but also in lipodystrophy. Although adipose tissue mass affects metabolic fluxes and participates in interorgan crosstalk, the role of energy metabolism within white adipose tissue for insulin resistance is less clear. Materials and methods A Medline search identified in vivo studies in humans on energy and lipid metabolism in subcutaneous (SAT) and visceral adipose tissue (VAT). Studies in adipocyte cultures and transgenic animal models were included for the better understanding of the link between abnormal energy metabolism in adipose tissue and insulin resistance. Results The current literature indicates that higher lipolysis and lower lipogenesis in VAT compared to SAT enhance portal delivery of lipid metabolites (glycerol and fatty acids) to the liver. Thus, the lower lipolysis and higher lipogenesis in SAT favour storage of excess lipids and allow for protection of insulin‐sensitive tissues from lipotoxic effects. In insulin‐resistant humans, enhanced lipolysis and impaired lipogenesis in adipose tissue lead to release of cytokines and lipid metabolites, ultimately promoting insulin resistance. Adipose tissue of insulin‐resistant humans also displays lower expression of proteins involved in mitochondrial function. In turn, this leads to lower availability of mitochondria‐derived energy sources for lipogenesis in adipose tissue. Conclusions Abnormal mitochondrial function in human white adipose tissue likely contributes to the secretion of lipid metabolites and lactate, which are linked to insulin resistance in peripheral tissues. However, the relevance of adipose tissue energy metabolism for the regulation of human insulin sensitivity remains to be further elucidated.